2007
DOI: 10.1111/j.1600-079x.2007.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on horseradish peroxidase‐catalyzed oxidation of melatonin: production of N1‐acetyl‐N2‐formyl‐5‐methoxykynuramine versus radical‐mediated degradation

Abstract: There is a growing body of evidence that melatonin and its oxidation product, N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK), have anti-inflammatory properties. From a nutritional point of view, the discovery of melatonin in plant tissues emphasizes the importance of its relationship with plant peroxidases. Here we found that the pH of the reaction mixture has a profound influence in the reaction rate and products distribution when melatonin is oxidized by the plant enzyme horseradish peroxidase. At pH 5.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
5
19
0
Order By: Relevance
“…Importantly, as has been shown previously for other substrates, 20 HRP can act on A2E at pH 5.5, the pH of lysosomes wherein the bisretinoids of RPE reside. We have characterized the structures of four of the largest degradation products; continued decline with time in the peak intensities attributable to these products indicated that enzyme-mediated cleavage was progressive.…”
Section: Discussionsupporting
confidence: 70%
“…Importantly, as has been shown previously for other substrates, 20 HRP can act on A2E at pH 5.5, the pH of lysosomes wherein the bisretinoids of RPE reside. We have characterized the structures of four of the largest degradation products; continued decline with time in the peak intensities attributable to these products indicated that enzyme-mediated cleavage was progressive.…”
Section: Discussionsupporting
confidence: 70%
“…3). Peak 1 correlates with hydroxymelatonin, which was previously identified by us and others [18–20]. Peak 2 correlates with AFMK, one of the main products of enzymatic and nonenzymatic oxidation of melatonin [18–25].…”
Section: Resultsmentioning
confidence: 65%
“…Recently, we demonstrated that the pH of the medium has a profound influence on the rate and products profile during the oxidation of melatonin [18]. For this reason, we studied how CPZ could affect the oxidation of melatonin at different pH.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been demonstrated that the metabolites of melatonin including N 1 ‐acetyl‐ N 2 ‐formyl‐5‐methoxykynuramine and N ‐acetyl‐5‐methoxykynuramine have effective antioxidants properties. It seems some of the antioxidative roles of melatonin could have been a consequence of its metabolites [23–25]. Jou et al.…”
Section: Discussionmentioning
confidence: 99%